Control Scheme and Performance Analysis of Dual-Frequency Single-Phase Grid-Connected Inverter Interfaced With Weak and Distorted Grids - Liyong Yang; Xiaojuan He; Peng Zhang; Shuo Liu (IEEE Access, 2020)
Grid impedance variation and voltage harmonics may cause instability of the grid-connected inverter system and reduce the grid current quality under weak grid. Switching losses and electromagnetic interference of inverter can be reduced by using lower switching frequency. However, it is a challenging task to achieve stable operation of LCL-type grid-connected inverter using the active damping method at the low switching frequency. In this paper, an improved control strategy is proposed for the dual-frequency inverter, which contains a power inverter and an auxiliary converter. For the proposed control strategy, the ability to suppress the influence of the grid voltage harmonics and the robustness against grid impedance variation are analyzed. In order to reduce the switching losses, the electrical energy is delivered to the power grid through the power inverter at a low switching frequency. By using the switching ripple compensation method and the grid voltage feedforward scheme, the switching current ripple caused by the power inverter and the current harmonics caused by the grid voltage harmonics can be suppressed. Since the filters used in the proposed inverter are all L type filters, the system stability is guaranteed under weak grid. The simulation and experimental results are provided to verify the effectiveness of the proposed grid-connected inverter system under weak grid.